Implementation of Counselling Guidance Program to improve Students' Discipline Character at SD 090 Cibiru Bandung City - Asep Ridwanuloh; Lusepi; Ayi Najmul Hidayat (AL-IBANAH, 2025)
This study investigates the implementation of the Counseling program at SD Negeri 090 Cibiru, Bandung, focusing on its role in developing students' character, particularly in terms of discipline and responsibility. The research is grounded in the growing importance of character education within the national curriculum and the behavioral challenges faced by students in today’s rapidly changing environment. A qualitative descriptive method was employed, with data gathered through observations, interviews with teachers, the school principal, and students, along with document analysis of school regulations and BK materials. Findings show that the BK program has contributed to improved student discipline—evident from reduced tardiness and better compliance with school rules. Students also demonstrated increased responsibility, shown in their independence in completing tasks and maintaining classroom cleanliness. Despite these positive outcomes, the study identifies gaps in consistency of implementation and limited parental involvement as ongoing challenges. Overall, the BK program proves to be an effective strategy for character building when implemented holistically and sustainably. This research highlights the importance of collaboration between schools, families, and communities in supporting character education, and emphasizes the need for continuous reflection and improvement to ensure long-term behavioral transformation among elementary students